Interaction of oxidative feed sanitizer with dietary methionine on growth and immune-responsiveness of broiler chickens - RAKESH THAKUR; A B MANDAL; A S YADAV (Indian Journal of Animal Sciences, 2016)
Acidified sodium chlorite (ASC), a well known sanitizer, reduces microbial load and improves energy bioavailability from fiber/lignin rich feedstuffs. However, ASC also reacts with sulphur containing amino acid methionine, the first limiting amino acid in maize-soy based diet. So the present experiment was conducted to assess the interaction of ASC with dietary methionine in terms of growth performance, meat quality and immune- competence of broiler chicks. A basal diet was formulated without methionine supplementation (otherwise adequate in all nutrients) and then treated with 3 levels of ASC (0, 100 and 250 ppm). Each ASC treated basal diet was supplemented without or with DL-methionine to meet 100 and 120% of NRC requirement of methionine in a 3 × 3 factorial design. Day-old broiler chicks (288) were divided into 36 groups of 8 chicks each and each dietary treatment was offered to 4 replicated groups. At 6 weeks of age, methionine supplementation produced significant increase in live body weight, weight gain and feed conversion ratio. Among meat quality parameters, thiobarbituric acid reactive substance value increased significantly upon ASC treatment and reduced by methionine supplementation at 120%. Among cut-up parts, neck yield increased significantly with increased level of methionine. Increase in methionine level also produced improvement in humoral and cell mediated immunity. Thus, it may be concluded that ASC treatment deteriorated oxidative stability of meat while methionine supplementation improved broiler performance, meat quality and immunocompetence